USE OF FLEXIBLE STICKS IN THE PREVENTION OF INFECTIONS IN PATIENTS WITH CENTRAL VENOUS CATHETER - Deise Cristina Furtado Liedke; Christiane Johnscher Niebel Stier (Universidade Federal do Paraná, 2000)
The work relates the use of flexible sticks in dressings of central venous catheter, in patients in the Intensive Care Unit. It shows that the technique, which was introduced during a period of high incidence of infections relating to central venous catheter, provided an opportunity to reduce the level of infections, controlled by the Hospital Infection Control Service. The work highlights that the new technique has been fully incorporated to the routine inside the hospital as a means to prevent and control infection in patients with central venous catheter.